Analysis of soil nailing using British Standard for slope stability - Zahirali Joomun (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study focus on influence on slope stability for factors such as; angles of slopes, soil type, inclination of nail, spacing between nails, length of nail, addition of external surcharge load on safety factor of the slope and usage of different code of practice.